Analisis Pentanahan Kaki Menara Transmisi 150 Kv Rembang-Blora Bertahanan Tinggi Dan Usaha Menurunkannya - Hajarsaputro, Nurcahyo; , Hasyim Asya'ri, S.T., M.T (2016)
This study was done to improve the value of grounding system resistance at the tower 150 KV high-voltage network installation towers along the path, the region Rembang-Blora substations as much as 92 towers. Grounding resistance lower leg useful as a shortcut to dampen the flow lightning strikes, grounding resistance transmission foot is as less than 5 ohms. Grounding resistance who exceed the value of the security is not assured air transmission line protection, back flashover is very likely to occur in this. Grounding resistance 150 KV transmission Rembang-Blora to experiencing of changein the parameters of several transmission foot high tower transmissionmore 5 ohms. The work done by PT. PLN (Persero) to lower the grounding resistance is to supervise and routine maintenance. Measurement tower of 150 KV transmission SUTT parent (GI) Rembang-Blora using tools, namely is Earth Tester. To obtain custody of approximately 5 ohm researchers perform calculations and repair. namely by adding a rod electrode (grounding) diameter 3 \ 4 inches. The measurement results showed 44 tower in need of repair and that it now adheres to the standard or less than 5 ohms.